2022
DOI: 10.1049/cmu2.12350
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term passenger flow forecasting using CEEMDAN meshed CNN‐LSTM‐attention model under wireless sensor network

Abstract: For a long time, the accurate prediction of passenger flow can provide early warning information for various industries such as the public service industry, tourism industry, and industrial business, thus opportunely arranging passengers and providing homologous services to relieve the overloading of places and the accidents caused by overcrowding of people. In recent years, by using the wireless sensor network to sense the passenger data in advance, the technique of machine learning and neural networks has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The CNN-LSTM Algorithm consists of the combination of two algorithms named CNN and LSTM. The CNN algorithm is a type of DL algorithm, and the LSTM algorithm is a Recurrent Neural Network (RNN) algorithm [36].…”
Section: Methodsmentioning
confidence: 99%
“…The CNN-LSTM Algorithm consists of the combination of two algorithms named CNN and LSTM. The CNN algorithm is a type of DL algorithm, and the LSTM algorithm is a Recurrent Neural Network (RNN) algorithm [36].…”
Section: Methodsmentioning
confidence: 99%
“…To characterize spatial characteristics, many scholars have introduced convolutional neural networks(CNN) into the field. Wang et al [41] proposed a CNN-LSTM model based on the attention mechanism; Wang et al [42] constructed a prediction model based on convolutional LSTM with K-mean clustering algorithm; Zhao et al [43] established a hybrid model based on CNN and residual network(ResNet). However, it was found that the urban rail network presents obvious non-Euclidean properties, and CNN is mostly applicable to Euclidean data with regular spatial structure, leading to the limitation of its spatial characteristics extraction capability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhao 14 optimized the LSTM based on Nadam and SGD algorithm, which improved the training efficiency and convergence rate of the model. In order to fully extract the spatial-temporal features of passenger flow distribution, Wang 15 proposed a CNN-LSTM model based on attention mechanism; Wang 16 combined the convolution LSTM with the K-means clustering algorithm; and Zhao 17 constructed a hybrid model based on convolutional neural network(CNN) and Residual network(ResNet). Ma 18 constructed a two-column model based on CNN and LSTM to finely extract the spatial and temporal features of the passenger flow sequence, but the input and output of the two-column structure are relatively independent, ignoring the interaction between different features, and the prediction accuracy decreased when applied to more complex scenarios.…”
Section: Introductionmentioning
confidence: 99%